2017
DOI: 10.1177/0954008317697367
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and photophysical study of new blue fluorescent poly(azomethine-1,3,4-oxadiazole)s containing dimethylamino groups

Abstract: New aromatic polyazomethines were synthesized by polycondensation reaction of a diamine containing 1,3,4-oxadiazole ring, namely, 4,4′-diamino-4″-[2-(4-phenoxy)-5-(4-dimethylaminophenyl)-1,3,4-oxadiazole)]triphenylmethane, with terephthalic aldehyde or bis(4-formylphenoxyphenyl)fluorene, by using N-methyl-2-pyrrolidinone (NMP) as solvent. The polymers were easily soluble in polar solvents, such as NMP, N, N-dimethylacetamide, or chloroform, and showed high thermal stability with the initial decomposition tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…Conjugated poly(azomethine)s have used in the production of polymeric light emitting diodes (PLED) 7,8 and solar cells 9,10 . Also, they have showed fluorescence properties because of conjuge π‐bonding 11–13 . Furthermore, poly (azomethine)s have the ability to form a good film 14,15 for high‐quantum efficiency, light emitting, sensitivity to photonic and electronic stimuli, macromolecular interaction and multi‐color emission properties when excited at certain wavelengths 16–18 .…”
Section: Introductionmentioning
confidence: 99%
“…Conjugated poly(azomethine)s have used in the production of polymeric light emitting diodes (PLED) 7,8 and solar cells 9,10 . Also, they have showed fluorescence properties because of conjuge π‐bonding 11–13 . Furthermore, poly (azomethine)s have the ability to form a good film 14,15 for high‐quantum efficiency, light emitting, sensitivity to photonic and electronic stimuli, macromolecular interaction and multi‐color emission properties when excited at certain wavelengths 16–18 .…”
Section: Introductionmentioning
confidence: 99%
“…This strongly limits their characterization in solution and their applications in some fields, especially those in which the polymers should be coated for solid‐state applications. Several researchers have shown that an adequate monomer design can improve the solubility of these polymeric materials through specific functionalizations such as meta ‐substitutions on the aromatic rings, and the incorporation of side groups, aliphatic moieties, flexible links, asymmetrical monomers, and bulky substituents along the main chains . However, as the flexibility of the chains increased, the glass‐transition temperature ( T g ) of the material should decreased.…”
Section: Introductionmentioning
confidence: 99%
“…In this line of thought, great findings were achieved by joining the electron donating fluorene with building blocks containing the electron withdrawing oxadiazole [13]. An overview of the literature data revealed that oxadiazole and fluorene-based chromophores were joined by a randomly [14,15,16] or alternately [17,18,19,20,21] manner by Suzuki or Still polycondensation, in various mixtures with other aromatic/heterocyclic moieties. Besides, polyfluorene with oxadiazole pendant units [22,23,24] or low molecular weight compounds [25,26,27] were also synthetized.…”
Section: Introductionmentioning
confidence: 99%